A Descriptive Study Risk Factors of Recurrent Lumbar Disk Herniation 1st April 2022 to 2nd April 2023 - Safi, Khyber (Journal of Health, Medicine and Nursing, 2024)
Purpose: The purpose of this study on recurrent lumbar disc herniation is to determine the causes, clinical findings, and incidence across different age groups above and below 60 years old, as well as gender. The aim is to evaluate the risk factors of recurrent disc herniation in the Afghani population. Methodology: To identify predictors for recurrent lumbar disc herniation (RLDH), a systematic review and meta-analysis were conducted based on existing evidence. The study aimed to provide pooled estimates that may assist various healthcare professionals, including researchers, surgeons, policymakers, caregivers, and patients, in identifying high-risk populations, preventing RLDH, and further investigating the underlying mechanisms. Findings: Risk factors for RLDH are under increasing investigation. Previous studies have examined various potential risk factors such as age, gender, body mass index (BMI), smoking, herniation type, diabetes, and herniation level. However, results from these studies have not always been consistent. For instance, while Kim et al. identified being male as a risk factor for RLDH, other studies did not find significant correlations. Inconsistencies also exist regarding smoking as a risk factor. This study aims to provide more reliable conclusions on these risk factors through a systematic approach. Unique Contribution to Theory, Practice and Policy: Understanding the risk factors associated with recurrent lumbar disc herniation is crucial for improving patient outcomes and reducing the burden on both individuals and society. By identifying and clarifying these risk factors, healthcare professionals can better tailor interventions, treatment plans, and preventive measures for individuals at high risk for RLDH. This study's findings may contribute significantly to the development of strategies aimed at mitigating the recurrence of lumbar disc herniation in the Afghani population.